2011
DOI: 10.1246/cl.2011.1456
|View full text |Cite
|
Sign up to set email alerts
|

Protonation-induced Cyclization of 1,8-Bis(arylethynyl)anthraquinones: Monopyrylium Salt Formation and Intensification of Donor–Acceptor Interaction

Abstract: We previously reported protonation-induced double cyclization reaction of 1,4-Ar 2 Aq and 1,5-Ar 2 Aq (Ar 2 Aq: bis(arylethynyl)anthraquinone) with strong acid HX that generated the corresponding dipyrylium salts [1,4- DA, DAD, and ADA (D: donor; A: acceptor) types of compounds are exciting materials, 1 and have been intensively studied in terms of fundamental research as well as potential applications, such as nonlinear optics (NLOs) and organic electronics. The electronic structure of DA, DAD, and AD A molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…The DCM layer was dried with sodium sulfate and filtered, and solvent was removed under vacuum. The crude product was purified using column chromatography with EtOAc/Hexane (30:70) as a white solid, 72% yield; mp 284−287 °C; Methyl-4-amino-3-chloro-6-(2-((4-fluorophenyl) sulfonamido) phenyl) picolinate (26). The compound 7 (30 mg, 0.11 mmol) was dissolved in DCM (3 mL) solvent, and DIPEA (23 μL, 0.13 mmol) and 4-fluoro benzenesulfonylchloride (21 mg, 0.11 mmol) were added simultaneously and stirred for 4 h at RT.…”
Section: ■ Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…The DCM layer was dried with sodium sulfate and filtered, and solvent was removed under vacuum. The crude product was purified using column chromatography with EtOAc/Hexane (30:70) as a white solid, 72% yield; mp 284−287 °C; Methyl-4-amino-3-chloro-6-(2-((4-fluorophenyl) sulfonamido) phenyl) picolinate (26). The compound 7 (30 mg, 0.11 mmol) was dissolved in DCM (3 mL) solvent, and DIPEA (23 μL, 0.13 mmol) and 4-fluoro benzenesulfonylchloride (21 mg, 0.11 mmol) were added simultaneously and stirred for 4 h at RT.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…Besides, one of the major research area for our group is to design and synthesize a new heterocyclic scaffold containing compounds for novel biological activity and material applications. 8 , 19 26 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a series of studies, Japanese scientists reported the electrophilic cyclization of 1-aryl ethynylanthra-quinones [16][17][18]. Here, protonation was performed on a wide range of substrates via the addition of bis(trifluoromethanesulfone)imide acid (TFSIH) in dichloromethane to give products that were stable in air.…”
Section: Chemical Propertiesmentioning
confidence: 99%
“…On the other hand, benzofuran derivatives are also present in many natural products and exhibit properties like physiological, pharmacological, and toxic. They also display many applications like sedatives, antioxidants , pharmaceuticals , cosmetics , molecular switches , and also for the building blocks of optical brighteners . In fact, several benzofuran ring systems bearing various substituents at the C‐2 position are widely distributed in nature.…”
Section: Introductionmentioning
confidence: 99%